Position paper: rationale for a focused attention on mental health of high-performance sports coaches - Kenttä, G.; Dieffenbach, K.; Bentzen, M.; Thompson, M.; Côté, J.; Mallett, C.; Olusoga, P. (International Sport Coaching Journal, 2024)
High-performance (HP) coaching has been described as "a complex, social, and dynamic activity that is not easily represented as a set of tangible and predictable processes." Coaches are not only responsible for extensive planning, monitoring, and leadership in a dynamic and complex environment but also have responsibility for supporting athlete development and safeguarding their athletes` overall health, well-being, and psychological and physiological safety. However, HP coaching is often considered an unsustainable profession, due to the levels of stress and subsequent mental health challenges that are frequently part of the role. Therefore, this position paper will focus on the concerns, challenges, and resources needed to prevent and manage mental ill-being and support the mental well-being of sport coaching professionals in HP sport, and provide recommendations for individuals, systems, and organizations that work with HP sport coaches.